2001
DOI: 10.1007/s11926-001-0069-3
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide and inflammatory mediators in the perpetuation of osteoarthritis

Abstract: Articular chondrocyte production of nitric oxide (NO) and other inflammatory mediators, such as eicosanoids and cytokines, are increased in human osteoarthritis. The excessive production of nitric oxide inhibits matrix synthesis and promotes its degradation. Furthermore, by reacting with oxidants such as superoxide anion, nitric oxide promotes cellular injury and renders the chondrocyte susceptible to cytokine-induced apoptosis. PGE(2) exerts anabolic and catabolic effects on chondrocytes, depending on the mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
152
0
5

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 242 publications
(167 citation statements)
references
References 59 publications
(58 reference statements)
3
152
0
5
Order By: Relevance
“…KG, Germany) before operation (baseline) and at 4,8,12,16, and 20 weeks after operation. At week 20 after surgery following the microdialysis experiment, the rats were sacrificed by deep anesthesia with sodium pentobarbital (50 mg/kg), then perfused intracardially with heparinized saline (400 mL) followed by freshly prepared 4% paraformaldehyde in 0.1 M phosphate-buffered saline, pH 7.4.…”
Section: Histopathological Examination Of Jointsmentioning
confidence: 99%
See 1 more Smart Citation
“…KG, Germany) before operation (baseline) and at 4,8,12,16, and 20 weeks after operation. At week 20 after surgery following the microdialysis experiment, the rats were sacrificed by deep anesthesia with sodium pentobarbital (50 mg/kg), then perfused intracardially with heparinized saline (400 mL) followed by freshly prepared 4% paraformaldehyde in 0.1 M phosphate-buffered saline, pH 7.4.…”
Section: Histopathological Examination Of Jointsmentioning
confidence: 99%
“…1,2 Studies had revealed a role of inflammatory process in the pathogenesis of OA, 3 and potential mediators were described. 4 Patients with rupture of the anterior cruciate ligament (ACL) develop posttraumatic OA of the knee. 5 Restoration of knee stability by reconstruction provides symptomatic relief, but does not decrease the incidence of degenerative changes of the ACL injured knee.…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, these results indicate that the ability of indomethacin to block NO-induced apoptosis and dedifferentiation is independent of the inhibition of COX-2 activity and PGE 2 production. DISCUSSION NO production in articular chondrocytes plays a central role in the pathophysiology of arthritis (5,8,9,36). High levels of nitrite/nitrate are found in the synovial fluid and serum of arthritis patients (37), and it has been shown that NO causes loss of a differentiated phenotype and apoptosis of articular chondrocytes (6,7,(12)(13)(14).…”
Section: Nsaids Inhibit Apoptosis and Dedifferentiation Independent Omentioning
confidence: 99%
“…Although the molecular mechanism is not yet clear, dedifferentiation of articular chondrocytes is believed to play a role in the pathophysiology of arthritis. In addition to dedifferentiation, increased apoptotic death of chondrocytes was observed in arthritic cartilage, and apoptosis is closely related to cartilage destruction (6, 7), indicating that chondrocyte apoptosis plays an important role in the pathogenesis of arthritis.NO is generally believed to be an important mediator of the dedifferentiation and apoptosis of articular chondrocytes in arthritic cartilage (5,8,9). NO is produced in chondrocytes by the action of proinflammatory cytokines, such as interleukin-1␤.…”
mentioning
confidence: 99%
See 1 more Smart Citation